The Implementation of Emotional Intelligence at Darussalam Modern Gontor Islamic Institution - Ahmad Hidayatullah Zarkasyi; Aghitsna Rahmatika; Citra Eka Wulandari (At-Ta'dib, 2021)
Emotional intelligence is a person's ability to manage responses, emotions, and interactions when dealing with other people. This intelligence requires the owner to process feelings and respect themselves and others so that they are able and understand how to place themselves in their environment. Because of emotional intelligence’s importance in life, Darussalam Modern Gontor Islamic Institution which is one of the Islamic boarding schools in Indonesia with a dormitory system is very concerned and tries to improve this intelligence in addition to intellectual and spiritual intelligence. Therefore, this study aims to explain the implementation of emotional intelligence in Darussalam Modern Gontor Islamic Institution and its implications for students. This research is a qualitative research with data collection techniques in the form of interviews, observation and documentation. Meanwhile, the data analysis method used is descriptive analysis technique. The results of this study indicate that emotional intelligence at Darussalam Modern Gontor Islamic Institution is improved through various activities undertaken by students for 24 hours. From here, students have self-awareness, self-management, empathy, and sympathy and have good social relationships with various kinds of students with different characters.